Tracing VAT-2008 program participants’ self development: Effect of social work program undergraduates intervention strategies - Shaffie, Fuziah; Md Ali, Ruzlan (Elsevier, 2015)
Research regarding violence amongst youth and teenagers had suggested the importance of designing and implementing effective intervention programs that takes into account the participants’ specific needs of the teenagers.The purpose of the study: to identify the effect of the VAT-2008 program on teenagers who were categorized as high-risk teenagers by their respective schools; to identify the VAT-2008 participants’ self development from the sosio-economy, values and personality aspects; to determine the factors that constraint the VAT-2008 participants from changing their attitudes.What are the effect of the VAT-2008 program on the high-risk school teenagers from the aspects of their self-development socio-economy, values, personality and change in attitude? This study was framed within the descriptive qualitative research approach.It adopted the exploratory field work research design in which primary data was collected via the open-ended questionnaires and supplemented by performing face-to-face interviews, using interview schedule which was constructed by the researchers, with the participants and their parents and/or family members.A significant percentage of the participants reported the VAT-2008 program had positively impact on their feelings of self-worth, level of confidence, and made them become a more independent and responsible individual.Participants had also confided that they become more responsible to their families and had realized the importance of working their ways to towards attaining a better and comfortable life.Each participant's case is unique.Despite reporting the positive impact of the program on them, nevertheless their experience participating in the VAT-2008 program had qualitatively different effect on their their self-development, socio-economy, values, personality and attitude. The interventions strategies implemented by the Social-Work undergraduates had indeed significantly touched their life journey.